Thyroid-Induced Worsening of Parkinsonian Tremor Resistant to Drugs and Subthalamic Nucleus Deep Brain Stimulation - Michal Minár; Peter Valkovič (Case Reports in Neurological Medicine)
Introduction. Symptoms of both hypothyroidism and thyrotoxicosis can be easily overlooked in patients with Parkinson’s disease (PD). We report on a patient whose parkinsonian tremor worsened and proved refractory not only to common treatment, but also to deep brain stimulation (DBS). Case Presentation. A 61-year-old woman with advanced PD underwent bilateral subthalamic DBS, with an excellent outcome. Twenty-one months after the surgery, however, patient’s resting/postural tremor markedly worsened. There was a slight improvement for 1 month after repeated adjustments of DBS parameters, but then the tremor worsened again. Since even a minimal increase of the dose of dopaminergic drugs caused extremely severe dyskinesias, an anticholinergic drug biperiden and benzodiazepine clonazepam were introduced, what helped for another month. With the onset of severe diarrhoea, a laboratory workup was performed. Thyrotoxicosis was detected. During treatment with the antithyroid agent carbimazole, the parkinsonian tremor clearly improved within two weeks. Conclusion. A hyperthyroid state can markedly exaggerate all forms of tremor, as well as other types of movement disorders. This condition can be overlooked or masked by other symptoms. Therefore, if the tremor in a patient with PD gradually worsens and proves resistant to the usual treatment, examine the thyroid gland.